Comparison of the Effect of Non-Surgical Periodontal Therapy on Periodontal Health Status and Glycemic Control between Diabetes Mellitus Type 1 and Type 2 - Ousama Aziz Ibrahim; Haneen Ali Kadhim; Farah K. Aloraibi (Indian Journal of Forensic Medicine & Toxicology, 2021)
Objectives. This study aims to compare the results of non-surgical periodontal therapy on the periodontalhealth status and glycemic control between diabetes mellitus type 1 (T1DM) and type 2 (T2DM).Methods. A total of 24 adult patients participated in this study. Patients divided into two groups, 12 patientsare diagnosed with T1DM, and 12 diabetic patients with T2DM. After 3 months non-surgical periodontaltreatment, the following parameters were investigated at baseline: glycosylated hemoglobin (HbA1c), plaqueindex (PI), bleeding on probing (BOP), gingival recession (GR), probing pocket depth (PPD), and clinicalattachment level (CAL). After baseline investigation, both groups received one stage full mouth scaling androot planning, combined with systemic Doxycycline, statistical analysis was performed by Student T-test.Results. By comparing between T1DM and T2DM at base line, and after 3 months non-surgical periodontaltherapy showed generally no significant differences with respect to periodontal parameters, while HbA1cvalues were always significantly higher in T1DM. By comparing of each parameter before- and 3 monthsafter non-surgical periodontal therapy with relation to the type of diabetes mellitus showed reduction ofgingival inflammation (PI, BOP), but there are no significant differences of probing pocket depth in bothdiabetic groups, glycemic control level HbA1c showed significant reduction only in diabetic patients Type 2.Conclusion. Results of the present study showed that non-surgical periodontal therapy in both diabetes typesdecreased gingival inflammation, no changes in periodontal pocket depth, but reduced glycemic controlsignificantly only on type 2 diabetes mellitus.